Influence of cytokinins in combination with GA3 onshoot multiplication and elongation of tea clone Iran 100 (Camellia sinensis (L.) O. Kuntze) - Gonbad, Reza Azadi; Sinniah, Uma Rani; Abdul Aziz, Maheran; Mohamad, Rosfarizan (Hindawi Publishing Corporation, 2014)
The use of in vitro culture has been accepted as an efficient technique for clonal propagation of many woody plants. In the present research, we report the results of a number of experiments aimed at optimizing micropropagation protocol for tea (Camellia sinensis (L.) O. Kuntze) (clone Iran 100) using nodal segments as the explant. The effect of different combinations and concentrations of plant growth regulators (PGR) (BAP, TDZ, GA3) on shoot multiplication and elongation was assessed. The influence of exposure to IBA in liquid form prior to transfer to solid media on rooting of tea microshoots was investigated. The results of this study showed that the best treatment for nodal segment multiplication in terms of the number of shoot per explant and shoot elongation was obtained using 3 mg/L BAP in combination with 0.5 mg/L GA3. TDZ was found to be inappropriate for multiplication of tea clone Iran 100 as it resulted in hyperhydricity especially at concentrations higher than 0.05 mg/L. Healthy shoots treated with 300 mg/L IBA for 30 min followed by transfer to 1/2 strength MS medium devoid of PGR resulted in 72.3% of shoots producing roots and upon transferring them to acclimatization chamber 65% survival was obtained prior to field transfer.